THE PATTERN OF TOPIC CHANGE IN INDONESIAN AND SINGAPOREAN CONVERSATION - Ulfa Putri Andalasia; Azwandi Azwandi; Irma Diani (JOALL (Journal of Applied Linguistics and Literature), 2019)
This research was analyze and discuss the pattern in conversation. Applied pattern of conversation is unpredictable, it is drawn the section and topics which used by participants. The objectives are drawn pattern of topic change, find out clues and describe aspect that influenced pattern of topic change in conversation. The method of this research was qualitative research, the data collected by recording and transcribing. The participants are Singaporean and Indonesian, the data are conversation both director and secretary. Data analyzed through ethnography methodology in communication and conversation analysis. Weather, this condition was quite different to the theory. First is pattern of topic change in formal conversation quite different to the previous study and theory. There found important section in each topic. This conclusion where has not explained before. Second is aspect influencing pattern of topic change are dominant participants, context, relation and time. The emphasis findings are there found several differences of pattern in topic change at the formal context. The important aspect is dominant participants. It was controlling of the conversation also take role in topic change. These results may affect by the background knowledge of the participants and the context of the conversation.Keywords:Topic changes, pattern in conversation and aspect influencing topic change